Characterization of rainfall spells for urban water management. (17th May 2012) - Chowdhury, Rezaul K.; Beecham, Simon
Abstract: Rainfall events and inter‐event spell properties were analysed in this study using observed daily rainfall sequences for Adelaide and Melbourne in Australia. First and higher order transitional probabilities of dry and wet days were also estimated. Various statistical moments of spells were estimated and compared between Adelaide and Melbourne. Six theoretical distributions were fitted to the dry and wet spells. These were geometric, compound geometric, generalized Pareto, logarithmic series, Polya and truncated negative binomial distributions. The probability of longer dry spells was found to be higher in Adelaide than in Melbourne. Mean dry spell length was found to be highest in summer, where 7 days and 5.5 days were observed in February in Adelaide and Melbourne respectively. Mean wet spell length was observed to be longer in Adelaide than in Melbourne during autumn and winter. The study revealed that dry and wet spells in Adelaide and Melbourne are best fitted by geometric and compound geometric distributions. The Polya distribution was also found to fit the Melbourne dry spell lengths and Adelaide wet spell lengths. The Implications of dry spell properties for urban water management (for example water sensitive urban design) are also discussed. Copyright © 2012 Royal Meteorological Society